The quotable Jefferson - Jefferson, Thomas, 1743-1826 (Princeton University Press, 2006)
More than any other Founding Father, Thomas Jefferson made his reputation on the brilliance of his writing. John Adams chose the 33-year-old Jefferson to draft the Declaration of Independence largely because of his "masterly Pen." The genius of the Declaration and Jefferson's later writings amply confirmed Adams's judgment. Few writers have said so much on so many subjects--and said it so well--as Jefferson. The Quotable Jefferson--the most comprehensive and authoritative book of Jefferson "ations ever published--demonstrates that as does no other book. Drawing primarily on The Papers of Thomas Jefferson, published by Princeton University Press, John Kaminski has carefully collected and cleverly arranged Jefferson's pronouncements on almost 500 subjects, ranging from the profound and public--the Constitution--to the personal and peculiar--cold water bathing. The Quotable Jefferson is the first book to put Jefferson's words in context with a substantial introduction, a chronology of Jefferson's life, the source of each "ation, an appendix identifying Jefferson's correspondents, and a comprehensive index. The main section of Jefferson "ations, which are arranged alphabetically by topic, is followed by three other fascinating sections of "ations: Jefferson on his contemporaries, his contemporaries on him, and Jefferson on himself. This book will delight the casual reader and browser, but it is also a serious and carefully edited reference work. Whatever the subject, if Jefferson said something memorable about it, you are likely to find it here.